Robotic Assistance in Unicompartmental Knee Arthroplasty Results in Superior Early Functional Recovery and Is More Likely to Meet Patient Expectations. (15th July 2021) - Crizer, Meredith P.; Haffar, Amer; Battenberg, Andrew; McGrath, Mikayla; Sutton, Ryan; Lonner, Jess H.
Abstract : Robotic technology has reduced the errors of implant alignment in unicompartmental knee arthroplasty (UKA), but its impact on functional recovery after UKA is poorly defined. The purpose of this study was to compare early functional recovery, pain levels, and satisfaction in UKA performed with either robotic assistance or conventional methods. A retrospective analysis was performed on 89 matched consecutive patients who underwent outpatient UKA by a single physician using either conventional instruments ( n = 39) or robotic methods ( n = 50), with otherwise identical perioperative protocols. Outcomes studied included Lower Extremity Functional Score (LEFS), new Knee Society Score (KSS), Knee Injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS-JR.), VR/SF-12, Visual Analog Scale (VAS) pain scores, and perioperative opioid consumption. Patients in the robotic cohort had superior early functional outcomes, with greater LEFS (conventional = 23; robotic = 31) at 1 week post-op p = 0.015 and KOOS-JR (conventional = 74; robotic = 81) at up to 6 months post-op p = 0.037 ; these two values remained statistically significant after mixed-model regression analysis p = 0.010 ; p = 0.023, respectively. At 1 year post-op, expectations were more likely to be met in those who received robotic assistance p = 0.06 . No differences were reported with respect to postoperative opioid usage p = 0.320, reoperations p = 1.00, and complications p = 0.628 . Robotic-assisted UKA resulted in more rapid recovery and less early postoperative pain and were more likely to meet expectations than conventional UKA, although functional differences equilibrated by 1 year postoperatively. Further follow-up is necessary to determine if implant durability is impacted by robotics.